Socioeconomics determinants of household carbon footprint in Iskandar Malaysia - Zen, Irina Safitri; Uddin, M. Salim; Al-Amin, Abul Quasem; Majid, Mohammad Rafee; Almulhim, Abdulaziz I.; Doberstein, Brent (Elsevier Ltd., 2022)
Understanding the complex links between socioeconomic variables and carbon emissions can reveal household spending and lifestyle patterns. This study oversees those issues and examines consumption patterns and their related variables such as climate change understanding, attitudes, and knowledge, in order to better comprehend the complicated linkages. This study revealed that eight socioeconomic elements influence a household’s carbon footprint: (i) household income (β = 0.476, p < 0.05), (ii) green attitudes (β = − 0.196, p < 0.05), (iii) residential space (β = 0.157, p < 0.05), (iv), education levels (β = 0.131, p < 0.05), (v) household’s tenure status by ownership (β = 0.130, p < 0.05), (vi) household’s age (β = 0.112, p < 0.05), (vii) size of household (β = 0.101, p < 0.05), and, (viii) female-headed household (β = − 0.077, p < 0.05). Approximately 83.6% of respondents are mindful of climate change, but only 2.6% correctly define it as a long-term shift in weather patterns. The study found that 82% of households are willing to change their consumption habits and lifestyle to reduce their household’s carbon footprint. In order to achieve a low carbon society, our research advocate a multipronged approach and policy action is crucial based on the results. Further, robust climate change educational and awareness programmes is decisive at the multilevel and scale in Malaysia to achieve its carbon emissions reduction target by 2050.